Harvey Potter's balloon farm - Harold, Jerdine Nolen; Buehner, Mark (New York : Lothrop, Lee & Shepard Books, 1993)
A child ventures out in the middle of the night to see how Harvey Potter grows his wonderful balloons.
Originally published in Never a worm this long by Heath Reading, D.C. Heath & Company. Reprinted by permission.
All Juvenile.
Keywords: Tall tales; Balloons -- Fiction; Farm life -- Fiction; Tall tales; Balloons -- Fiction; Farm life -- Fiction